MiR-1281 is involved in depression disorder and the antidepressant effects of Kai-Xin-San by targeting ADCY1 and DVL1. Issue 3 (March 2023) - Chen, Chao; Xu, Yuan-jie; Zhang, Shang-rong; Wang, Xiao-hui; Hu, Yuan; Guo, Dai-hong; Zhou, Xiao-jiang; Zhu, Wei-yu; Wen, Ai-Dong; Tan, Qing-Rong; Dong, Xian-Zhe; Liu, Ping
Abstract: Kai-Xin-San (KXS) is a Chinese medicine formulation that is commonly used to treat depression caused by dual deficiencies in the heart and spleen. Recent studies indicated that miRNAs were involved in the pathophysiology of depression. However, there have been few studies on the mechanism underlying the miRNAs directly mediating antidepressant at clinical level, especially in nature drugs and TCM compound. In this study, we identified circulating miRNAs defferentially expressed among the depression patients (DPs), DPs who underwent 8weeks of KXS treatment and health controls (HCs). A total of 45 miRNAs (17 were up-regulated and 28 were down-regulated) were significantly differentially expressed among three groups. Subsequently, qRT-PCR was used to verify 10 differentially expressed candidate miRNAs in more serum samples, and the results showed that 6 miRNAs (miR-1281, miR-365a-3p, miR-2861, miR-16-5p, miR-1202 and miR-451a) were consistent with the results of microarray. Among them, miR-1281, was the novel dynamically altered and appeared to be specifically related to depression and antidepressant effects of KXS. MicroRNA-gene-pathway-net analysis showed that miR-1281-regulated genes are mostly key nodes in the classical signaling pathway related to depression. Additionally, our data suggest that ADCY1 and DVL1 were the targets of miR-1281. Thus, based on the discovery of miRNA expression profiles in vivo, our findings suggest a new role for miR-1281 related to depression and demonstrated in vitro that KXS may activate cAMP/PKA/ERK/CREB and Wnt/β-catenin signal transduction pathways by down-regulating miR-1281 that targets ADCY1 and DVL1 to achieve its role in neuronal cell protection.